Blood pressure monitoring in kidney transplantation: a systematic review on hypertension and target organ damage. Issue 7 (25th March 2021) - Pisano, Anna; Mallamaci, Francesca; D'Arrigo, Graziella; Bolignano, Davide; Wuerzner, Gregoire; Ortiz, Alberto; Burnier, Michel; Kanaan, Nada; Sarafidis, Pantelis; Persu, Alexandre; Ferro, Charles J; Loutradis, Charalampos; et al.
Abstract: Background: Few studies show that ambulatory blood pressure (BP) monitoring (ABPM) is superior to office BP (oBP) measurements to predict target organ damage and cardiovascular (CV) events in kidney transplant recipients (KTRs). We performed a systematic review aimed at determining the potential associations between BP recordings by different methods and renal and CV outcomes in this population. Methods: Major medical databases were searched for studies enrolling adult KTRs undergoing 24-h ABPM compared with office or home BP measurements. The main outcomes were associations between different BP recordings and renal and CV outcomes. Additionally, any association between the circadian BP pattern (dipping/non-dipping status) and outcomes was assessed. Results: Twenty-two studies (2078 participants) were reviewed. Among 12 studies collecting data on renal endpoints, 10 studies found that BP assessed by ABPM was a stronger predictor of renal function decline, assessed by serum creatinine and/or creatinine clearance or estimated glomerular filtration rate, than traditional office measurements. Twelve studies analysed the relation between different BP recordings and CV target organ damage and reported robust correlations between echocardiographic abnormalities (i.e. left ventricular mass index) and 24-h ABPM, but not with office BPs. Furthermore, 24-h ABPM correlated better than oBP with markers of vascular damage, such as carotid intima-media thickness, diffuse thickening and endothelial dysfunction. Additionally, an abnormal circadian BP pattern (non-dippers and reverse dippers) identified a group of kidney recipients at risk for kidney function loss and CV abnormalities. Conclusions: In our systematic review, ABPM reflected target organ damage more closely than oBP in KTRs. Furthermore, an altered circadian BP profile associated with renal and CV target organ damage.